UNDERSTANDING INDEPENDENCE ATTITUDES, AUDIT ETHICS, ACCOUNTABILITY AND COMPETENCE AS DETERMINANTS OF QUALITY AUDITORS: A LITERATURE REVIEW - Rohim, Muhammat Hanafi Fathur; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aims to review the literature on the factors that influence the quality of an auditor, with a focus on understanding attitudes of independence, audit ethics, accountability, and competence. As a profession that is important in ensuring the integrity and transparency of financial reports, quality auditors are indispensable in maintaining public confidence in company financial information. Data collection techniques were carried out using the literary review method. This study identified and analyzed scientific publications, journals, and related literature from a certain period. Relevant data is then collected, analyzed, and synthesized to present significant findings regarding the factors influencing auditor quality. The results of this study indicate that a deep understanding of independence is an important factor in determining the quality of an auditor. Good audit ethics leads to honest, fair, and responsible behavior in performing audit tasks. High competence in auditing is also a crucial factor. Auditors with adequate knowledge and auditing skills will be more able to carry out their duties accurately and efficiently. Accountability is important in ensuring that auditors are held accountable for their actions and decisions. An accountable auditor will be more careful and careful in assessing, testing, and verifying the company's financial statements. In conclusion, understanding attitudes of independence, audit ethics, accountability, and competence collectively are important determinants in determining an auditor's quality. This research provides valuable insights for practitioners, academics, and regulators in understanding the factors that can improve audit quality and maintain the integrity of the auditor profession.